Earthquake preparedness of households and its predictors based on health belief model - Masoumeh Rostami-Moez; Mohammad Rabiee-Yeganeh; Mohammadreza Shokouhi; Amin Dosti-Irani; Forouzan Rezapur-Shahkolai (BMC, 2020)
Abstract Background Earthquakes are one of the most destructive natural disasters in which many people are injured, disabled, or died. Iran has only 1 % of the world's population, but the percentage of its earthquake-related deaths is absolutely higher. Therefore, this study aimed to determine the level of earthquake preparedness of households and its predictors using the Health Belief Model (HBM). Methods This observational descriptive and analytical study was conducted on 933 households in Hamadan province, located in the west of Iran, in 2019. Multi-stage cluster random sampling was used for selecting the participants. The inclusion criteria were being at least 18 years old and being able to answer the questions. A questionnaire was used for data collection including earthquake preparedness, awareness of earthquake response, predictors of earthquake preparedness based on the HBM, and demographic information. Analysis of variance, independent t-test, and a linear regression model was used. Results The mean age of participants was 38.24 ± 12.85 years. The average score of earthquake preparedness was low (approximately 30%). There was a significant relationship between earthquake preparedness and gender (P < 0.001), homeownership (P < 0.001), marriage status (P < 0.001), education (P < 0.001), and previous earthquake experience (P < 0.001). Regarding the HBM constructs, perceived benefits (P < 0.001), cues to action (P < 0.001), and self-efficacy (P < 0.001) were significant predictors of earthquake preparedness. Conclusions Earthquake preparedness was insufficient. Besides, perceived benefits, cues to action, and self-efficacy were predictors of earthquake preparedness. These predictors can be taken into account, for designing and implementing related future interventions.